Preliminary sensory evaluation of salty crackers with grape pomace flour - Palma, M.Lidia (2021)
Grape pomace, a by-product of winemaking, contains numerous chemical compounds with high nutritional value and potential benefits for human health, which enable its use for product enrichment in different industries from cosmetics to food. The aim of this study was to incorporate the grape pomace flour of the Touriga Nacional and Arinto grapes varietals from Alentejo region of Portugal in a recipe for salty crackers, which were submitted to sensory evaluationby applying a hedonic test to 53 individuals. The results of the evaluation show a clear tendency of preference for the crackers with 10% of grape pomace, both the Touriga Nacional and Arinto samples, which presented the highest result averages